PENGARUH KEPEMILIKAN INSTITUSIONAL, DEWAN KOMISARIS INDEPENDEN, DAN KOMITE AUDIT TERHADAP NILAI PERUSAHAAN SEKTOR PERTAMBANGAN - Fitri Amaliyah; Eliada Herwiyanti (UNIB Press, 2019)
The purpose of the study was to determine whether there are effects of institusional ownership, independent commissioner and the audit board to the value of the company. This type of research is correlational research, with quantitative research. This study uses secondary data taken from the IDX website data. The sample used in this study proved 60 companies consisting of the mining sector during the 2-year observation period. The sampling technique was carried out using the purposive sampling method. The analytical method used is multiple linear regression analysis with an analysis tool using SPSS 22. The results of this study indicate audit committees variables have a significant effect on firm value. While the institusional ownership and independent commissioner variables are not significant to the value of the company.